LANGUAGE, EMOTION, AND ALGORITHMS: THE DYNAMICS OF COMMUNICATION IN THE SOCIAL MEDIA ERA - Ria Wuri Andary,; Ara Auza, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The social media phenomenon has transformed the way humans communicate. Algorithms, inherent in each platform, play a crucial role in shaping the information users receive, often prioritizing content that triggers emotional responses. This study aims to analyze the dynamics of communication in the social media era through the diverse interactions between language, emotion, and algorithms. Using a descriptive narrative literature review approach, this study examines how language evolves on social media, the role of emotion in content virality, and how algorithms reinforce emotional polarization. The results show that language on social media tends to be more concise, visual, and emotionally expressive, with a predominant use of emojis, abbreviations, and hyperbolic style. Emotions, particularly strong ones such as anger or emotion, have been shown to be key drivers of content virality, which are then amplified by algorithms to increase user engagement. This interaction creates a cycle in which algorithms select emotional language, generate viral content, and in turn, encourage users to imitate that communication style, forming a new digital communication culture. The conclusion of this study is that language, emotion, and algorithms mutually reinforce each other in shaping the way digital communication is perceived, with significant implications for digital literacy and communication ethics. Therefore, the development of more ethical and socially conscious algorithms is necessary to create a healthier digital space.